Impacts of COVID-19 on the Life and Work of Healthcare Workers During the Nationwide Partial Lockdown in Vietnam - Pham, Quan Thi; Le, Xuan Thi Thanh; Phan, Tam Chi; Nguyen, Quang Nhat; Ta, Nhung Kim Thi; Nguyen, Anh Ngoc; Nguyen, Thao Thanh; Nguyen, Quynh Thi; Le, Huong Thi; Luong, Anh Mai; Koh, David; Hoang, Men Thi; et al. (Frontiers in Psychology, 2021)
Background: Healthcare workers are frontline responders facing a disproportionate increase in occupational responsibilities during the COVID-19 pandemic. Added work-related stress among healthcare personnel may lead to personal and work-related repercussions, such as burnout or decreased quality of care for patients; however, little is known about how the COVID-19 pandemic affects the daily work and life of these workers. This study aimed to evaluate the personal and occupational impacts of the COVID-19 induced partial lockdown in Vietnam among hospital staff. Methods: A cross-sectional web-based study was carried out to collect demographic data and the personal and job impacts of respondents during the second week of national lockdown in April 2020. Snowball sampling technique was applied to recruit 742 hospital staff. The exploratory factor analysis (EFA) was used to examine the validity of the instrument. Results: Of the 742 respondents, 21.2% agreed that “working attitude well-maintained,” followed by 16.1% of respondents who reported that there were “enough employees at work.” Only 3.2% of respondents agreed that “their work was appreciated by society.” Furthermore, healthcare workers in the central region were less likely to have experienced “Avoidance of disclosure and discrimination related to COVID-19” than other areas (Coef. = – 0.25, CI: −0.42 to −0.07). Being women also had a negative association with scores in “Avoidance of disclosure and discrimination related to COVID 19” domain (Coef. = −0.27, CI: −0.43 to −0.12) while having a positive association with “negative attitude towards working conditions” domain (Coef. = 0.19, CI: 0.09 to 0.3). In addition, working in administrative offices (Coef. = 0.20; 95% CI = 0.05 to 0.36) and infectious departments (Coef. = 0.36; 95% CI = 0.09 to 0.63) had a positive association with “Increased work pressure due to COVID 19” domain. Conclusion: These findings revealed marginal impacts of the COVID-19 pandemic on the work and life of hospital staff in Vietnam. Furthermore, this study highlighted the importance of implementing preventive strategies during the nationwide partial lockdown to manage hospital admissions and the burden on healthcare workers. Finally, this study characterizes targeted demographics that may benefit from appreciation by employers and society during a national pandemic.